2020
DOI: 10.1192/bjo.2020.132
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine treatment for individuals with treatment-resistant depression: longitudinal qualitative interview study of patient experiences

Abstract: Background Ketamine has recently received considerable attention regarding its antidepressant and anti-suicidal effects. Trials have generally focused on short-term effects of single intravenous infusions. Research on patient experiences is lacking. Aims To investigate the experiences over time of individuals receiving ketamine treatment in a routine clinic, including impacts on mood and suicidality. Method Twelve fee-paying patients with treatment-resistant depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Consistent with other qualitative studies on ketamine treatment (26)(27)(28)(29), respondents were often overwhelmed by the "side effects" of esketamine. Using this specific terminology for the acute psychoactive effects of ketamine implied that these are 10.3389/fpsyt.2022.948115 undesirable, reducing the likelihood for patients to recognize and interpret such experiences as potentially therapeutic, and of sharing their experiences with staff afterward, particularly since some participants in our study suggested their subjective experiences were therapeutically valuable.…”
Section: Preparation and Educationsupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with other qualitative studies on ketamine treatment (26)(27)(28)(29), respondents were often overwhelmed by the "side effects" of esketamine. Using this specific terminology for the acute psychoactive effects of ketamine implied that these are 10.3389/fpsyt.2022.948115 undesirable, reducing the likelihood for patients to recognize and interpret such experiences as potentially therapeutic, and of sharing their experiences with staff afterward, particularly since some participants in our study suggested their subjective experiences were therapeutically valuable.…”
Section: Preparation and Educationsupporting
confidence: 67%
“…Recently, a number of qualitative studies investigated the experiences of patients undergoing IV ketamine treatment of alcohol use disorder (AUD) (16), suicidal ideation (26), major depressive disorder (MDD) (15, 17), and TRD (27)(28)(29). Most described the phenomenology of ketamine's acute effects; other themes included adverse effects (26)(27)(28)(29), perceived therapeutic mechanisms (16,26,29), patient attitudes, motivations, expectations (16, [27][28][29], and barriers and facilitators of (es)ketamine treatment (16,29). With one exception (ketamine treatment of AUD) (16), most qualitative studies did not capture in detail how patients experience the ketamine treatment and which conditions facilitate optimal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…24,53 We included 11 controlled and uncontrolled trials, case series, and case reports on maintenance oral ketamine treatment, including 199 unipolar (approximately 93%) and bipolar (approximately 7%) patients with treatmentresistant depression. 11,12,25,28,31,32,34,35,37,43,52 Duration and frequency of treatment varied widely, from 6 weeks to 3 years and from 3 times a day to once a month. In some studies frequency was individually tailored, in some dosing was individually tailored, and in some both were.…”
Section: Resultsmentioning
confidence: 99%
“…Two controlled trials, one uncontrolled trial, and six case series and reports presented results of maintenance treatment within the first 6 months after initial response. 12,25,28,32,34,35,37,43,52 Although the RCTs were not designed to study maintenance treatment, in both studies ketamine treatment was offered for more than 4 weeks, therewith meeting our intervention criteria. In the first RCT, including 40 patients, antidepressant effects were superior for ketamine versus diclofenac after 3 weeks of treatment when measured by the Hospital Anxiety and Depression Score (HADS).…”
Section: Resultsmentioning
confidence: 99%
“…They should also consider patients’ perspectives; therefore, patient report outcomes should be measured. Particularly interesting would be how patients perceive the treatment and its short- and long-term effects, as well as what their hopes and fears are [ 89 ]. The downstaging concept is presented in Figure 4 .…”
Section: Discussionmentioning
confidence: 99%